SAT0327 Baseline characteristics and reasons for apremilast prescription in a large italian cohort of psoriatic arthritis patients. (12th June 2018) - Favalli, E.G.; Zuccaro, C.; Biggioggero, M.; Selmi, C.; Bucci, R.; D'onofrio, F.; Carlino, G.; Santo, L.; Semeraro, A.; Monti, S.; Mazzotta, D.; Atzeni, F.; et al.
Abstract : Background: There are no real-world data for the profiling of patients with psoriatic arthritis (PsA) receiving the phosphodiesterase-4 inhibitor apremilast. Objectives: To retrospectively evaluate the baseline characteristics and the reasons for apremilast prescription in a large Italian multicenter cohort of PsA cases (R eal-life AP remilast for P soriatic arthritis E valuation R egistry, RAPPER). Methods: Data were retrospectively extracted from the RAPPER registry which includes all PsA cases treated with apremilast in 11 Italian tertiary rheumatology centres between January 2017 and December 2017. Descriptive analysis of baseline characteristics of study population included demographics, previous treatments before apremilast, pattern of PsA involvement, disease activity indices, and prevalence of comorbidities (computed by the Rheumatic Disease Comorbidity Index [RDCI] 1 ). Reasons for apremilast choice were also analysed. Results: We studied 97 patients with PsA (61% women; mean [±standard deviation, SD] age 56.7±11.9 years; mean disease duration 10±13.1 years) who received apremilast as first-line targeted disease modifying drug (51.5%) or after the failure of at least one biologic agent (48.5%). In 75%, 33%, 11%, and 63% of patients there were articular (57% asymmetric oligoarthritis; mean Disease Activity in PSoriatic Arthritis [DAPSA] 22.55±11.55), entheseal (mean Leeds Enthesitis Index [LEI] 2.63±1.42), axial (mean Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] 6.02±2.40), and skin/ungueal (mean body surface area [BSA] 1.71±3.44) involvement, respectively. Two thirds (64%) of patients had at least one comorbidity (mean RDCI 1.20) and the prevalence of conditions is reported in table 1. The main reasons for apremilast prescription were contraindication to biologic agents (66%), lack of poor prognostic factors (35%), comorbidities (34%), risk of infections (33%), and history of malignancy (22.6%), whereas a preference for an oral drug drove the choice only in 7% of patients. Conclusions: Based on our analysis, apremilast is mainly used in PsA with oligoarthritis, enthesitis, mild skin involvement, and low risk of disease progression, carrying comorbidities (especially history of infections and malignancies) with contraindications to the use of biologic drugs. Reference: [1] England BR, Sayles H, Mikuls TR, et al. Validation of the rheumatic disease comorbidity index. Arthritis Care Res2015;67(6):865–72. Disclosure of Interest: None declared